Effectiveness of interventional reproductive and sexual health education among school going adolescent girls in rural area - Rutuja M Phulambrikar; Anup Lahanubhau Kharde; Varsha N Mahavarakar; Deepak B Phalke; Vaishali D Phalke (Wolters Kluwer Medknow Publications, 2019)
Background: Most adolescents lack access to age- and sex-appropriate health information which is vital for young people to make informed decisions about their reproductive sexual health. Objectives: The study objective was to study the effectiveness of the interventional reproductive and sexual health education on knowledge, attitude, and menstrual practices of school-going adolescent girls. Materials and Methods: It was an interventional study consisting of a pretest, intervention session, and posttest conducted among 400 school-going adolescent girls in a rural area of Maharashtra. Results: There was a statistically significant increase in knowledge, attitude, and practice median scores following intervention (P < 0.05). Conclusions: Age- and sex-appropriate health education programs can facilitate the development of healthy reproductive and sexual behavior patterns among adolescents through the enhancement of knowledge and development of right attitude.